P84 Towards cell based therapy for α1-antitrypsin deficiency through targeted bi-allelic gene correction in human iPS cells. (6th September 2011) - Rashid, S T; Yusa, K; Strick-Marchand, H; Rouhani, F J; Marciniak, S J; Miranda, E; Ordonez, A; Hannan, N; Alexander, G; di-Santo, J; Bradley, A; Lomas, D A; et al.
Abstract : Introduction: Human induced pluripotent stem cells (hIPSCs) represent a unique opportunity for regenerative medicine since they offer the prospect of generating unlimited quantities of cells for autologous transplantation as a novel treatment for a broad range of disorders. We have previously developed disease specific human hepatocyte-like cells by reprogramming dermal fibroblasts taken from individuals with PiZ α1-antitrypsin deficiency. The resulting cells recapitulated the protein misfolding and intracellular polymer formation that characterise this disease (Rashid et al, J Clin Invest 2010;120 :3127–36). However, use of iPS cells in treatment of individuals with PiZ α1-antitrypsin deficiency would also require correction of the underlying genetic abnormality in a manner fully compatible with clinical applications. The methods currently available, such as homologous recombination, lack the necessary efficiency and also leave residual sequences in the targeted genome. Aim: (1). To correct the genetic mutation responsible for PiZ α1-antitrypsin deficiency in human IPS cells in a clinically relevant way. (2). To investigate the potential of using corrected hIPS derived liver cells for cell based therapy by studying their in vivo function. Method: The genetic defect responsible for PiZ α1-antitrypsin deficiency (Glu342Lys) was targeted using a combination of engineered Zinc finger nucleases and a piggyBac vector in patient specific hiPSCs. Corrected cells were differentiated to hepatocytes using a previously optimised chemically defined in vitro platform. Assessment of phenotypic correction was then made in vitro as well as in vivo. Results: We demonstrate here for the first time an efficient gene editing technique capable of restoring normal structure, function and secretion of α1-antitrypsin in subsequently derived liver cells without leaving residual exogenous sequences in the targeted hiPSC genome. Moreover injection of corrected hiPS derived liver cells into a mouse model of liver injury confirmed their potential for functional capacity in vivo. Importantly none of the transplanted mice showed evidence of tumour formation. Conclusion: Our results provide proof of principle for the potential of combining hiPSCs with gene therapy to generate cells for autologous cell based treatment of α1-antitrypsin deficiency in humans.